Handbook of Exoplanets 2017
DOI: 10.1007/978-3-319-30648-3_82-1
|View full text |Cite
|
Sign up to set email alerts
|

Interferometric Space Missions for Exoplanet Science: Legacy of Darwin/TPF

Abstract: DARWIN/TPF is a project of an infrared space-based interferometer designed to directly detect and characterize terrestrial exoplanets around nearby stars. Unlike spectro-photometric instruments observing planetary transits, an interferometer does not rely on any particular geometric constraints and could characterize exoplanets with any orbital configuration around nearby stars. The idea to use an infrared nulling interferometer to characterize exoplanets dates back to Bracewell (1978), and was extensively stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 90 publications
0
6
0
Order By: Relevance
“…They found that the red edge detectability ranged from 1% to 12% in observations and models. For space-based telescopes such as the Terrestrial Planet Finder/Darwin concepts (Beichman et al, 2007;Defre `re et al, 2017), the exposure times would be *100 h to reach a sufficient spectral precision (<3%) with a spectral resolution (k/Dk) of 25 for an Earth at 10 parsecs distance (Arnold et al, 2002). If detected, seasonal variations would be especially informative.…”
Section: Candidate Biogenic Gases and Their Concentrationsmentioning
confidence: 99%
“…They found that the red edge detectability ranged from 1% to 12% in observations and models. For space-based telescopes such as the Terrestrial Planet Finder/Darwin concepts (Beichman et al, 2007;Defre `re et al, 2017), the exposure times would be *100 h to reach a sufficient spectral precision (<3%) with a spectral resolution (k/Dk) of 25 for an Earth at 10 parsecs distance (Arnold et al, 2002). If detected, seasonal variations would be especially informative.…”
Section: Candidate Biogenic Gases and Their Concentrationsmentioning
confidence: 99%
“…They are listed along with their predicted observational properties in Table 3. The size of this sample doubles (Defrère et al 2018b), if one assumes a tighter inner working angle of 1 mas (0.25 × λ/B), which brings in potentially warmer planets with more favorable contrasts. A more detailed characterization of the true VIKiNG discovery and characterization potential is beyond the scope of this paper that only aims at introducing a new instrument concept.…”
Section: The Viking Surveymentioning
confidence: 99%
“…The proposed facilities would use a variety of technologies to achieve the high contrast and high angular resolution required for direct imaging of other Earths: starlight suppression with a coronograph or a starshade, or interferometry. These projects build on the heritage of many previously studied missions, notably the Terrestrial Planet Finder/Darwin concepts (Defrère et al 2018). Now that the occurrence rate of temperate rocky planets is known (Dressing & Charbonneau 2015;Bryson et al 2021), the time is ripe to pursue a flagship mission to characterize them in more detail.…”
Section: Observing Biosignatures With a Next-generation Telescopementioning
confidence: 99%